The Construction of Islamic State Law in the 5.0 Era from the Perspective of Maqasid al-Shariah - Ja'far, A. Kumedi; Muhammad Majdidin, Rijah; Santoso, Rudi; Hidayat, Taufik (KnE Social Sciences, 2024)
The discourse on Islamic constitutional law is consistently captivating and remains relevant for discussion. Islam, as a religion of mercy for all creation, takes the Quran and Hadith as its primary guidance without providing a specific qath’i (definite) pattern for formulating a state. Nonetheless, Islam has presented several general principles that can serve as the foundation and align with the objectives of Sharia in shaping a system of governance. This includes principles of justice (al-adalah), equality before the law (musawah), democratic consultation (as-syura), and the upholding of human rights and freedoms (al-hurriyah). This research aims to describe the principles of Islamic constitutional law while examining the characteristics of laws that can be implemented for Islamic societies as per the developments toward the era 5.0. Utilizing a qualitative research approach based on both digital and classical literature sources rooted in Islamic teachings (turats), this study formulates that the ideal Islamic constitutional law in the era 5.0, after adhering to its principles, should be dynamic, humanistic, and substantial. This assertion is substantiated by several laws that have been implemented, particularly in Indonesia, significantly contributing to the creation of harmony and tranquillity among its diverse population. Keywords: era 5.0, Islamic constitutional law, Maqasid Sharia